LEADERSHIP TRAINING - Magalhães, Thuany Cristine; Rodolpho, Daniela (Revista Interface Tecnológica, 2025)
The article addresses the critical importance of leadership training in modern organizations and explores several effective strategies for developing leadership skills. The evolution of the concept recognizes the urgency of adaptable, future-oriented leaders in an ever-changing business environment. An approach focused on the identification and development of key competencies is highlighted as key. This includes communication skills, emotional intelligence, decision-making ability, and interpersonal skills. In addition, the importance of self-awareness and continuous feedback in the leadership development process is recognized. The article also shows that leadership is the ability to inspire, influence, and guide others to achieve common goals. It involves knowing how to make effective decisions, communicate a clear vision, and motivate teams to succeed. Effective leadership also incorporates elements of empathy, authenticity, and adaptability. It emphasizes the importance of continuous evaluation and adaptation of leadership training strategies to meet the specific needs of the organization and the work environment. It highlights the lack of an ongoing commitment to leadership development as a key investment in the organization’s future success.